Efektivitas penggunaan bahan ajar pada materi bencana Tanah longsor melalui strategi snow balling Di smk negeri tulung - Lestari, Puji; , Drs. Suharjo, M.S (2016)
This research is conducted in order to know the effectiveness of teaching material on disaster by using Snow Balling learning strategy in SMK Negeri 1 Tulung. This research is a quantitative research using One Group Pre test Post test Design. Quantitative research is a research using numbers as the data which then analyzed. This kind of research is a research which intended to explain phenomena using numeric data, then analyzed using statistic. This research is conducted in experiment 2 (Disaster Prepared School Exstracuriculer) class with 21 students and Experiment 1 (TKJ kelas A) class with 21 students which the learning process uses teaching material through Snow Balling strategy. The result of the research is the effectiveness teaching material in Land Slide Disaster through Snow Balling strategy seen from average score of effective post test. This effectiveness is aimed to the extracuricular students Sekolah Siaga Bencana. Average post test score of experiment class is 92,05 and average pos test score of control class is 81,74 which fulfill standard score requirement. This research is also use Wilxocon and Mann-Whitney test which obtained probability 0,000, shows that there is a significant effect and difference between experiment 1 class and experiment class 2. Thus, Ho is rejected and Ha is accepted.